Dinamika dan Tantangan Penanaman Nilai-Nilai Moderasi Beragama dalam Konteks Pendidikan Agama Islam - Zeni Faridah; Ahmad Rizqi (Journal of Transdisciplinary Studies in Religion and Education, 2025)
This study aims to analyze the dynamics and challenges of instilling the value of religious moderation through Islamic Religious Education (PAI) in Indonesia. The method employed is library research, incorporating content analysis of various relevant primary and secondary sources. The results show that the values ​​of moderation, national commitment, tolerance, anti-violence, and respect for tradition have been integrated into the PAI curriculum, but its implementation still faces obstacles such as the dominance of cognitive approaches, limited teacher competency, and external environmental influences. Therefore, a comprehensive strategy is needed, including strengthening teacher capacity, promoting digital literacy, and fostering collaboration between stakeholders, so that PAI can shape a generation that is religious, tolerant, and inclusive